Analisis Sumber Penyebab Kesalahan Berbahasa Pada Konten Youtube Nadia Omara Dalam Meningkatkan Keterampilan Berbicara - Irfanda Siti Amaliyafitri; Diena San Fauziah (Politeknik Kampar, 2024)
This research discusses the analysis of language errors based on their sources and causes. This research aims to determine the source and cause of language errors from Nadia Omara's YouTube content